2007
DOI: 10.3113/fai.2007.0669
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Lesions of the Talus: Results of Repeat Arthroscopic Debridement

Abstract: This is the first series specifically assessing patients who have had repeat arthroscopic debridement of osteochondral lesions of the talus, using the same debridement technique by a single surgeon. Our results question the assumption that repeat arthroscopic debridement yields poor results. They also provide a baseline for the newer chondral and osteochondral transplantation techniques to compare to at the medium term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 14 publications
3
65
2
Order By: Relevance
“…This allowed comparison with other studies in which success rates were also reported according to the final outcome rather than the reoperation rate 11,14,19 . The AOFAS score of the patients who underwent a reoperation (median, 80) was similar to the score following repeat procedures reported by Savva et al (mean,81) 39 . Finally, univariate analysis was used to assess outcome predictors, as multivariate regression analysis could not be performed because of sample size restrictions.…”
Section: Discussionsupporting
confidence: 68%
“…This allowed comparison with other studies in which success rates were also reported according to the final outcome rather than the reoperation rate 11,14,19 . The AOFAS score of the patients who underwent a reoperation (median, 80) was similar to the score following repeat procedures reported by Savva et al (mean,81) 39 . Finally, univariate analysis was used to assess outcome predictors, as multivariate regression analysis could not be performed because of sample size restrictions.…”
Section: Discussionsupporting
confidence: 68%
“…128,190,346 Th e AOFAS score of the patients who underwent a reoperation (median, 80) was similar to the score following repeat procedures reported by Savva et al (mean,81). 341 Finally, univariate analysis was used to assess outcome predictors, as multivariate regression analysis could not be performed because of sample size restrictions.…”
Section: Discussionsupporting
confidence: 56%
“…The anterior portals can be combined with a posterolateral portal. 129,341 Alternatively, a twoportal hindfoot arthroscopic approach with the patient in the prone position is applied to treat OCDs located far posteriorly. 432 However, these procedures require more experience.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated the consistency of the results obtained with the treatment of osteochondral lesions through debridement and microfractures, with mean AOFAS score of 86.8 points, achieving 80.2% excellent and good results 36 ; however, significant deterioration of results was observed after 4.2 years of the procedure 17 …”
Section: Prognostic Factorsmentioning
confidence: 97%